Mobilization of autologous and allogeneic peripheral blood stem cells for transplantation in haematological malignancies using biosimilar G‐CSF - Schmitt, Michael; Hoffmann, Jean-Marc; Lorenz, Katrin; Schmitt, Anita (Vox sanguinis, 2016)
Background and Objectives Biosimilars of the granulocyte colony stimulating factor (G?CSF) filgrastim were approved by the European Medicines Agency (EMA) for registered indications of the originator G?CSF, including prevention and treatment of neutropenia, as well as mobilization of peripheral blood stem cells in 2008. Nevertheless, there is still an ongoing debate regarding the quality, efficacy and safety of biosimilar G?CSF. Materials and Methods This article is a meta?analysis of clinical studies on the use of biosimilar G?CSF for mobilization and transplantation of haematopoietic stem cells as available in public databases. All data sets were weighted for the number of patients and parameters and then subjected to statistical meta?analysis employing the Mann?Whitney U?test followed by the Hodges?Lehmann estimator to assess differences between biosimilar and originator G?SCF. Results A total of 1892 individuals, mostly with haematological malignancies but also including 351 healthy donors have been successfully mobilized for autologous or allogeneic stem cell transplantation using biosimilar G?CSF (ZarzioTM: 1239 individuals; RatiograstimTM/TevagrastimTM: 653 individuals). A total of 740 patients with multiple myeloma, 491 with non?Hodgkin's lymphoma (NHL), 150 with Hodgkin's lymphoma (HL) and other diseases are included in this meta?analysis, as well as 161 siblings and 190 volunteer unrelated donors. For biosimilar and originator G?CSF, bioequivalence was observed for the yield of CD34+ stem cells as well as for the engraftment of the transplants. Conclusion Biosimilar G?CSF has equivalent effects and safety as originator G?CSF.